2017
DOI: 10.1007/s11205-017-1697-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Unemployment and Insecure Jobs on Well-Being and Health: The Moderating Role of Labor Market Policies

Abstract: Labor market insecurities have been growing in Europe and previous research has illustrated that unemployment and insecure jobs negatively affect individuals' wellbeing and health. Although empirical evidence suggests that these effects vary substantially across different welfare states, we still know little about the moderating role of specific labor market policies. Taking a cross-national comparative perspective, this article investigates how passive and active labor market policies (PLMP, ALMP) as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 37 publications
7
96
0
Order By: Relevance
“…Within the general population, being employed has consistently been linked to better mental health and wellbeing [Backhans & Hemmingsson, 2012;Creed & Macintyre, 2001;Feather & O'Brien, 1986;Heinz et al, 2018;McKee-Ryan et al, 2005;Murphy & Athanasou, 1999;Paul & Moser, 2009;Voßemer et al, 2018;Wanberg, 2012], with greater benefits associated with higher levels of job satisfaction [Faragher et al, 2005]. As longterm outcomes in terms of mental health and well-being in employed adults with ASD is poorly understood, we monitored changes in mental health and well-being over time in newly employed adults with ASD, a population rarely represented in previous research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the general population, being employed has consistently been linked to better mental health and wellbeing [Backhans & Hemmingsson, 2012;Creed & Macintyre, 2001;Feather & O'Brien, 1986;Heinz et al, 2018;McKee-Ryan et al, 2005;Murphy & Athanasou, 1999;Paul & Moser, 2009;Voßemer et al, 2018;Wanberg, 2012], with greater benefits associated with higher levels of job satisfaction [Faragher et al, 2005]. As longterm outcomes in terms of mental health and well-being in employed adults with ASD is poorly understood, we monitored changes in mental health and well-being over time in newly employed adults with ASD, a population rarely represented in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Employment represents a milestone in human development, providing opportunities to expand social networks, develop financial independence, and to give life meaning. The association between employment and better mental health and well-being outcomes is well established in the general population [Backhans & Hemmingsson, 2012;Creed & Macintyre, 2001;Feather & O'Brien, 1986;Heinz et al, 2018;Helliwell & Huang, 2014;McKee-Ryan, Song, Wanberg, & Kinicki, 2005;Murphy & Athanasou, 1999;Paul & Moser, 2009;Voßemer et al, 2018;Wanberg, 2012;Wulfgramm, 2014], with meaningful employment identified as a protective factor against depression and other forms of psychological distress [van der Noordt, IJzelenberg, Droomers, & Proper, 2014]. However, employment may not be associated with improved mental health outcomes in people with ASD.…”
Section: Employment Mental Health and Well-beingmentioning
confidence: 99%
“…Eventually, when examining the effect heterogeneity across different countries, for policy making it is not only relevant whether there are differences across countries, but also which country-specific characteristics cause these differences. Previous literature shows that some economic macro-level factors like employment protection legislation (EPL), gross domestic product (GDP), unemployment rate, subjective and objective income inequality as well as other social policies do moderate the effects of fixed-term employment on well-being (Carr and Chung 2014;Voßemer et al 2018;Karabchuk and Soboleva 2019;Täht et al 2019). Nevertheless, we lack knowledge on whether besides the perceived income inequality, there are other cultural country-level characteristics explaining the variation.…”
Section: Introductionmentioning
confidence: 90%
“…On a different note, differences in unemployment benefits between countries have been found to be a factor that moderates the relationship between poor macroeconomic conditions and subjective well-being (Morgan 2018;Carr and Chung 2014;Wulfgramm 2014). Voßemer et al (2017) found that considerable unemployment benefits can mitigate the negative effects that unemployment has on subjective wellbeing.…”
Section: National and Regional Variationsmentioning
confidence: 99%